2023
DOI: 10.3390/v15102007
|View full text |Cite
|
Sign up to set email alerts
|

RNA Editing-Dependent and -Independent Roles of Adenosine Deaminases Acting on RNA Proteins in Herpesvirus Infection—Hints on Another Layer of Complexity

Vlatka Ivanišević,
Lidia Žilić,
Marina Čunko
et al.

Abstract: The Adenosine Deaminases Acting on RNA (ADAR) catalyze the posttranscriptional deamination of adenosine residues to inosine in double-stranded RNAs (dsRNAs, A-to-I editing), preventing the overactivation of dsRNA sensor molecules and interferons. RNA editing is the cornerstone of innate immunity that distinguishes between self and non-self (virus), and it is essential for normal regulation of cellular homeostasis. Although much is already known about the role of ADAR proteins in RNA virus infection, the role o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 101 publications
1
3
0
Order By: Relevance
“…Figure 1). This is also consistent with the stable ADAR1 expression levels in cells infected with HSV-1 or HSV-2 observed by Nachmani et al [39], but in contrast to cells infected with HCMV [39] or with other herpesviruses in which different isoforms of ADAR1 are induced [33]. Furthermore, in most other cells tested, we did not observe an increase but rather a decrease of ADAR1 after infection with HSV-1.…”
Section: Adar1 Is Required For Efficient Hsv-1 Replicationsupporting
confidence: 93%
See 3 more Smart Citations
“…Figure 1). This is also consistent with the stable ADAR1 expression levels in cells infected with HSV-1 or HSV-2 observed by Nachmani et al [39], but in contrast to cells infected with HCMV [39] or with other herpesviruses in which different isoforms of ADAR1 are induced [33]. Furthermore, in most other cells tested, we did not observe an increase but rather a decrease of ADAR1 after infection with HSV-1.…”
Section: Adar1 Is Required For Efficient Hsv-1 Replicationsupporting
confidence: 93%
“…The role of ADAR1 has been intensively studied in RNA viruses because of the inevitable dsRNA stage of their replication, and it has been shown that ADAR1 exerts both proand antiviral activity, in an editing-dependent and editing-independent manner [32,33]. For example, ADAR1 plays an important role in suppressing apoptosis, PKR activation and RLR signaling in cells infected with various RNA viruses, including measles virus (MV), influenza A virus (IAV), vesicular stomatitis virus (VSV), flaviviruses, etc.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations